Adrenal Gland Function and Dysfunction During COVID-19 - Kanczkowski, Waldemar; Gaba, Waqar Haider; Krone, Nils; Varga, Zsuzsanna; Beuschlein, Felix; Hantel, Constanze; Andoniadou, Cynthia; Bornstein, Stefan R. (Hormone and Metabolic Research, 2022)
The coronavirus disease 2019 (COVID-19) pandemic is currently one of the major health concerns worldwide accounting for many deaths and posing a great social and economic burden. Early activation of adrenal hormone secretion is pivotal to surviving systemic microbial infections. In addition, clinical studies demonstrated that glucocorticoids might also be beneficial in reducing disease progression and life deterioration in certain patients with COVID-19. Recent studies demonstrated that SARS-CoV-2 might target the adrenal glands, raising the possibility that at least some COVID-19 complications may be associated with adrenal dysfunction. Whether SARS-CoV-2 infection might cause adrenal dysfunction remains unknown. Histopathological examinations provided evidence that SARS-CoV-2 infection might indeed cause certain structural damage to the adrenal glands, especially concerning its vascular system. However, since no widespread cellular damage to cortical cells was observed, it is less likely that those changes could lead to an immediate adrenal crisis. This assumption is supported by the limited number of studies reporting rather adequate cortisol levels in patients with acute COVID-19. Those studies, however, could not exclude a potential late-onset or milder form of adrenal insufficiency. Although structural damage to adrenal glands is a rarely reported complication of COVID-19, some patients might develop a critical illness-related corticosteroid insufficiency (CIRCI), or iatrogenic adrenal insufficiency resulting from prolonged treatment with synthetic glucocorticoids. In this mini-review article, we aimed at describing and discussing factors involved in the adrenal gland function and possible dysfunction during COVID-19.
Keywords: SARS-CoV-2; CIRCI; PAI; adrenal insufficiency; HPA axis